Impacts of High Concentration, Medium Duration Coal Mine Fire Related PM on Cancer Incidence: 5-Year Follow-Up of the Hazelwood Health Study - Pei Yu (SAGE Publishing, 2021)
No studies have investigated the cancer outcomes from high level medium duration coal mine fire fine particulate matter ⩽2.5 µm in diameter (PM 2.5 ) exposure. We included 2208 Morwell residents (exposed) and 646 Sale residents (unexposed) who participated in the Hazelwood Health Study Adult Survey. Competing risk regression models were used to evaluate relationships between coal mine fire exposure and cancer incidence, adjusting for known confounders. There were 137 cancers in the exposed and 27 in the unexposed over 14 849 person-years of follow-up. A higher risk of cancer incidence was observed for Morwell participants (HR = 1.67 [95% CI 1.05-2.67]), but no evidence to suggest associations between PM 2.5 exposure and incidence of all cancers (HR = 1.02 [95% CI 0.91-1.13]), or site-specific cancers. There is no strong evidence that exposure to high concentrations of mine fire-related PM 2.5 over a prolonged period could explain the higher risk in exposed population in this study.